Craniocervical dystonia questionnaire (CDQ-24): development and validation of a disease-specific quality of life instrument. Issue 5 (16th April 2004) - Müller, J; Wissel, J; Kemmler, G; Voller, B; Bodner, T; Schneider, A; Wenning, G K; Poewe, W
Abstract : Objective: To develop and test a questionnaire for measuring quality of life in patients with craniocervical dystonia. Methods: A 29-item pool was developed based on semi-structured interviews of patients with cervical dystonia (CD) and blepharospasm (BSP). This preliminary questionnaire was administered to 203 consecutive patients with CD and BSP from Austrian dystonia and botulinum toxin outpatient clinics. For scale generation, a combination of exploratory factor and cluster analysis was applied. This resulted in the 24-item version of the instrument (CDQ-24) based on five subscales: Stigma, Emotional wellbeing, Pain, Activities of daily living, and Social/family life. The validity and reliability of the CDQ-24 was assessed in 231 consecutive patients with CD and BSP different from those examined with the preliminary questionnaire. This second survey included the CDQ-24, a generic QoL instrument (SF-36) and clinical rating scales. Sensitivity to change was analysed in 51 previously untreated (de novo) patients four weeks and one year following the first botulinum toxin treatment. Results: Internal consistency reliability was satisfactory for all subscales, with values of Cronbach's α ranging from 0.77 to 0.89. The CDQ-24 subscales showed moderate to high correlations with those SF-36 subscales measuring similar aspects (Pearson's correlation r = 0.50–0.73; p<0.001, each). Sensitivity to change was confirmed by highly significant improvements of all CDQ-24 subscores in the de novo patients from baseline to four week follow up. One year follow up data revealed a stable improvement. Conclusion: The CDQ-24 is the first fully validated and disease specific questionnaire to evaluate quality of life of patients with cervical dystonia and blepharospasm and we propose its use in clinical trials as well as in daily clinical practice.